Identification of interchangeable cross-species function of elongation factor-1 alpha promoters in Babesia bigemina and Babesia bovis. Issue 1 (December 2016) - Silva, Marta; Knowles, Donald; Suarez, Carlos
Abstract Background Tick-borneBabesia bigemina is responsible for acute and potentially lethal hemolytic disease in cattle. The development of genetic manipulation tools necessary to the better understanding of parasite biology is currently limited by the lack of a complete parasite genome and experimental tools such as transfection. Effective promoters, required to regulate expression of transgenes, such as theelongation factor-1 alpha (ef-1α ), have been identified in other apicomplexans such asBabesia bovis andPlasmodium falciparum. Methods TheB. bigemina ef-1a locus was defined by searching a partial genome library ofB. bigemina (Sanger Institute). Presence of an intron in the 5' untranslated region was determined by 5' Rapid Amplification of cDNA Ends (RACE) analysis. Promoter activity was determined by measurement of luciferase expression at several time points after electroporation, efficiency of transfections and normalization of data was determined by quantitative PCR and by the percentage of parasitized erythrocytes. Results Theef-1α locus contains two identical head to headef-1α genes separated by a 1.425 kb intergenic (IG) region. Significant sequence divergence in the regions upstream of the inverted repeats on each side of theB. bigemina IG region suggest independent regulation mechanisms for controlling expression of each of the twoef-1α genes. Plasmid constructs containing the 5' and 3' halves of the IG regions controlling the expression of the luciferase gene containing a 3' region of aB. bigemina rap-1a gene, were generated for the testing of luciferase activity in transiently transfected parasites. Both halves of theef-1α IG region tested showed the ability to promote high level production of luciferase. Moreover, bothB. bigemina ef-1α promoters are also active in transiently transfectedB. bovis and conversely, aB. bovis ef-1α promoter is active in transiently transfectedB. bigemina. Conclusions Collectively these data demonstrate the existence of two distinct promoters with homologous and heterologous promoter function inB. bigemina andB. bovis which is described for the first time inBabesia species. This study is of significance for development of interspecies stable transfection systems forB. bigemina and forB. bovis .